2019
DOI: 10.1111/nph.15964
|View full text |Cite
|
Sign up to set email alerts
|

Grasses and fire: the importance of hiding buds

Abstract: Additional Supporting Information may be found online in the Supporting Information section at the end of the article. Fig. S1 Mean effect size of the different variables for the models of postfire mortality and resprouting.Methods S1 Statistical methods.Notes S1 The relation between the presence of rhizomes and the photosynthetic pathway.Please note: Wiley Blackwell are not responsible for the content or functionality of any Supporting Information supplied by the authors. Any queries (other than missing mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…We found that the ability to resprout post-fire was not significantly associated with either C 3 or C 4 photosynthetic pathways, matching previous work using a smaller sample (Pausas and Paula, 2020). As in that work, we found that bud position was indeed related to resprouting ability, with a significantly higher proportion of resprouting species having buds belowground in the form of rhizomes as predicted.…”
Section: Accepted Articlesupporting
confidence: 89%
“…We found that the ability to resprout post-fire was not significantly associated with either C 3 or C 4 photosynthetic pathways, matching previous work using a smaller sample (Pausas and Paula, 2020). As in that work, we found that bud position was indeed related to resprouting ability, with a significantly higher proportion of resprouting species having buds belowground in the form of rhizomes as predicted.…”
Section: Accepted Articlesupporting
confidence: 89%
“…Under such regimes, the most likely fire response would be resprouting as short fire intervals would prevent seedlings and saplings of reaching maturity (Bellingham & Sparrow, 2000;Bond & Midgley, 2001Pausas & Keeley, 2014). Location, protection, and number of buds are main drivers of post-fire resprouting and adult individuals can resprout from aerial, basal or below-ground buds, given that the meristematic tissues survive the high temperatures caused by fire (Clarke et al, 2013;Clarke et al, 2015;Charles-Dominique et al, 2015;Pausas et al, 2018;Pausas & Paula, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some native species may be susceptible to fire (e.g. C3 grasses, Moore et al 2019), with responses depending on the location of regenerating buds (Pausas & Paula 2020). Resprouting capacity, particularly for C3 species, may also be negatively impacted by drought (Prober et al 2004; Moore et al 2019).…”
Section: Resultsmentioning
confidence: 99%